Improving student and faculty communication: the impact of texting and electronic feedback on building relationships and the perception of care - Jennie M. Carr; Karen Santos Rogers; Gibbs Kanyongo (Association for Learning Technology, 2021)
Students perceive care as a quality of highly effective faculty, and building positive relationships is essential to a successful college experience. However, many college students report never having developed caring relationships with faculty. We propose faculty have an opportunity to use technology to help build caring relationships in an effort to improve overall academic success. The majority of research on student-faculty interaction has primarily focused on determining what kinds of interactions students have with faculty. The aim of this study was to explore students' perceptions of care and the role safe texting and electronic feedback played in building student-faculty relationships. A mixed-methods approach was used with college student participants (n = 307) to answer the following research questions: (1) What actions by faculty constitute "caring"? (2) What role does technology play in students feeling "cared for"? The findings indicate that safe texting platforms and electronic feedback had a positive impact by increasing accessibility and direct contact.